The Developing Progress of Australian Cellular Agriculture in 2023—2024 - TAN Hong-zhuo; FANG Zhong-xiang; YI Cui-ping (Liang you shipin ke-ji)
Human consumption non-sustainable products has been beyond the bearing capacity of our planet. Cellular agriculture would provide an opportunity to diversify our food system, is expected to improve the sustainability of food supply, and can reduce ethical and moral issues associated with over-consuming animal-based foods. Cellular agriculture is still in an embryonic stage in Australia, but has huge potential. In this paper,we have explained why developing cellular agriculture is important from 6 aspects: food safety, reduced forest area, preventing biodiversity loss, mitigating climate change, improving public health and promoting animal welfare. We have also introduced 3 main technology challenges that Australia agriculture is facing: culture medium for cells, achieving desired taste and texture, and access to infrastructure. We have summarized the latest progress of Australian cellular agriculture in terms of technology, management, sector development, and talent cultivation, emphasizing the need to move forward in five areas: cllaboration, government support, investment, scaling up, and consumer acceptance. Future tasks for cellular agriculture include cultivating a still workforce, deepening inter-disciplinary research and open access, building large-scale manufacturing capabilities, creating a farorable policy environment, establishing a public regulatory framework and increasing societal acceptance. There are two key points for 2024: (1) developing a value chain ecosystem for Australia cellular agriculture; (2) raising the appeal for its investment and construction in this sector.